2010
DOI: 10.2353/ajpath.2010.090829
|View full text |Cite
|
Sign up to set email alerts
|

Endogenous Angiogenesis Inhibitor Vasohibin1 Exhibits Broad-Spectrum Antilymphangiogenic Activity and Suppresses Lymph Node Metastasis

Abstract: During cancer progression, the angiogenesis that occurs is involved in tumor growth and hematogenousdistant metastasis, whereas lymphangiogenesis is involved in regional lymph node metastasis. Angiogenesis is counterregulated by various endogenous inhibitors; however, little is known about endogenous inhibitors of lymphangiogenesis. We recently isolated vasohibin1 as an angiogenesis inhibitor intrinsic to the endothelium and further demonstrated its anticancer activity through angiogenesis inhibition. Here, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
73
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 80 publications
(81 citation statements)
references
References 37 publications
6
73
2
Order By: Relevance
“…Intravenous infusion of a viral vector encoding the human VASH1 gene was reported to have inhibited lymph node metastasis in a xenograft model of mice with cancer cells (Heishi et al 2010). In the present study, however, no significant difference was found in VASH1 expression between cases with and without lymph node metastasis.…”
Section: Discussioncontrasting
confidence: 53%
See 1 more Smart Citation
“…Intravenous infusion of a viral vector encoding the human VASH1 gene was reported to have inhibited lymph node metastasis in a xenograft model of mice with cancer cells (Heishi et al 2010). In the present study, however, no significant difference was found in VASH1 expression between cases with and without lymph node metastasis.…”
Section: Discussioncontrasting
confidence: 53%
“…Other studies reported a similar association in upper urinary tract carcinoma and prostate carcinoma, identifying VASH1 as a recurrence and prognostic marker (Miyazaki et al 2012;Kosaka et al 2013). In NSCLC, association of high VASH1 expression with short PFS and OS was reported (Heishi et al 2010). In uterine corpus carcinoma, the VASH1 expression was reported to be higher as the differentiation is poorer, but its correlation has not been analyzed yet (Yoshinaga et al 2008).…”
Section: Discussionmentioning
confidence: 99%
“…The administration of exogenous VASH1 strongly inhibits pathological and physiological angiogenesis without any significant side effects (Hosaka et al, 2009;Kimura et al, 2009;Shen et al, 2006;Watanabe et al, 2004;Yamashita et al, 2006). Most recently, we showed that VASH1 exhibits anti-lymphangiogenic activity and inhibits lymph node metastasis (Heishi et al, 2010). We also isolated VASH2, a homologue of VASH1 that displays more than 50% amino acid similarity to VASH1 Sato and Sonoda, 2007;Shibuya et al, 2006).…”
Section: Introductionmentioning
confidence: 92%
“…Subsequently, the supernatant was subjected to ELISA. The detailed procedure for the measurements carried out is described elsewhere (Heishi et al, 2010).…”
Section: Elisa For Vash1-svbp Complexmentioning
confidence: 99%
“…Plasma samples were collected, and their VASH1 levels were determined by ELISA. The ELISA for VASH1 was described previously [12].…”
Section: Methodsmentioning
confidence: 99%